False mystics : deviant orthodoxy in colonial Mexico - Jaffary, Nora E., 1968- (Engendering Latin America., 2004)
False Mystics provides a history of popular religion, race, and gender in colonial Mexico focusing on questions of spiritual and social rebellion and conformity. Nora E. Jaffary examines more than one hundred trials of "false mystics" whom the Mexican Inquisition prosecuted in the seventeenth and eighteenth centuries. While the accused experienced many of the same phenomena as bona fide mystics-visions, sacred illness, and bouts of demonic possession-the Mexican tribunal condemned them nevertheless. False Mystics examines why the Catholic church viewed the accused as deviants and argues that this categorization was due in part to unconventional aspects of their spirituality and in part to contemporary social anxieties over class and race mixing, transgressions of appropriate gendered behavior, and fears of Indian and African influences on orthodox Catholicism. Jaffary examines the transformations this category of heresy underwent between Spain and the New World and explores the relationship between accusations of "false" mysticism and contemporary notions of demonic possession, sickness, and mental illness. False Mystics illuminates the challenges that popular religion and individual spirituality posed to both the institutional church and the colonial social order